Augmenting anticipatory action and resilience in fragile, data-challenged, conflict-affected settings, in the case of Tigray, Ethiopia - McTough, Mitchell; Zerihun, Zenawi; Wood, R. (Tropical and Subtropical Agriculture, Natural Resource Management and Rural Development, 2024)
The conflict in Ethiopia's Tigray region ignited on November 4, 2020, quickly escalated from localized skirmishes into a complex civil war with profound humanitarian, political, and regional implications. Involving national forces, regional militias, and foreign troops, the conflict has resulted in mass displacement and widespread human rights violations. Although reliable data is scarce, estimates suggest that between 400,000 to 850,000 people had lost their lives, both civilians and combatants. This study critically examines the multifaceted effects of the conflict, particularly on climate adaptation and resilience in urban areas hosting internally displaced persons (IDPs). The research focuses on the city of Mekelle (pop. 537,822), the capital of the region, which hosts over 224,000 I DPs in both informal settlements and managed tented camps (IOM, 2023). It underscores the challenges of information reliability and highlights a strategic shift in humanitarian action, emphasizing conflict-sensitive, evidence-based anticipatory action (AA) over traditional "no regrets" responses. By leveraging innovative data tools such as citizen science and remote sensing, this research provides actionable insights into the vulnerability of I DP-hosting communities, aiming to enhance crisis response and resilience strategies in such contexts.